Schizosaccharomyces pombe cdc20(+ )encodes DNA polymerase ɛ and is required for chromosomal replication but not for the S phase checkpoint - D’Urso, Gennaro (The National Academy of Sciences of the USA, 1997)
In fission yeast both DNA polymerase alpha (pol α) and delta (pol δ) are required for DNA chromosomal replication. Here we demonstrate that Schizosaccharomyces pombe cdc20(+) encodes the catalytic subunit of DNA polymerase epsilon (pol ɛ) and that this enzyme is also required for DNA replication. Following a shift to the restrictive temperature, cdc20 temperature-sensitive mutant cells block at the onset of DNA replication, suggesting that cdc20(+) is required early in S phase very near to the initiation step. In the budding yeast Saccharomyces cerevisiae, it has been reported that in addition to its proposed role in chromosomal replication, DNA pol ɛ (encoded by POL2) also functions directly as an S phase checkpoint sensor [Navas, T. A., Zhou, Z. & Elledge, S. J. (1995) Cell 80, 29–39]. We have investigated whether cdc20(+) is required for the checkpoint control operating in fission yeast, and our data indicate that pol ɛ does not have a role as a checkpoint sensor coordinating S phase with mitosis. In contrast, germinating spores disrupted for the gene encoding pol α rapidly enter mitosis in the absence of DNA synthesis, suggesting that in the absence of pol α, normal coordination between S phase and mitosis is lost. We propose that the checkpoint signal operating in S phase depends on assembly of the replication initiation complex, and that this signal is generated prior to the elongation stage of DNA synthesis.